2015
DOI: 10.1007/s10803-015-2428-3
|View full text |Cite
|
Sign up to set email alerts
|

Initial Ophthalmic Findings in Turkish Children with Autism Spectrum Disorder

Abstract: Children with autism spectrum disorders (ASD) frequently have ophthalmologic disorders. Due to poor cooperation with ophthalmological examination, ocular abnormalities in such children may be overlooked. We retrospectively studied the records of 324 patients diagnosed as ASD that underwent ophthalmological examination between January 2011 and November 2014 at Dr. Sami Ulus Maternity and Children Research and Training Hospital, Ankara, Turkey. Ophthalmic pathology was noted in 26.9% of patients with ASD, of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 10 publications
3
24
0
Order By: Relevance
“…Table 3 documents the prevalence of refractive errors and strabismus found in each of the studied groups. As the table shows, Kabatas et al (2015) found that 26.9% of their participants had refractive errors and 8.6% strabismus (squint); Black et al (2013) found 27% of their sample to have Kielinen et al (2004) noted that 22.9% had refractive errors. The study of visually impaired individuals found 11% of their sample to meet the diagnostic criteria for autism (Mukaddes et al 2007).…”
Section: The Prevalence Of Visual Impairment In People With Asdmentioning
confidence: 98%
See 4 more Smart Citations
“…Table 3 documents the prevalence of refractive errors and strabismus found in each of the studied groups. As the table shows, Kabatas et al (2015) found that 26.9% of their participants had refractive errors and 8.6% strabismus (squint); Black et al (2013) found 27% of their sample to have Kielinen et al (2004) noted that 22.9% had refractive errors. The study of visually impaired individuals found 11% of their sample to meet the diagnostic criteria for autism (Mukaddes et al 2007).…”
Section: The Prevalence Of Visual Impairment In People With Asdmentioning
confidence: 98%
“…The evidence relating to the prevalence of sight loss in people with ASD since 2000 is limited to seven studies (Black et al 2013;Ezegwui et al 2014;Ikeda et al 2013;Kabatas et al 2015;Kielinen et al 2004;Milne et al 2009;Mukaddes et al 2007). Table 1 details the quality of the evidence based on the criteria proposed in the Quality Assessment Tool for Quantitative Studies (Thomas et al 2004).…”
Section: The Prevalence Of Visual Impairment In People With Asdmentioning
confidence: 99%
See 3 more Smart Citations